Analysis of Whatsapp Chat Usage as Court Evidence - Deviriana, Benedicta Ingrid; Nurdianti, Dinda; Tirta Chandra, Fioren; Nagib, Muhamad; Danella , Xena (Green Publisher Indonesia, 2025)
This article examines the use of WhatsApp chats as evidence in Indonesian court proceedings, a matter of growing relevance due to technological advancements in digital communication. The research evaluates the legal validity and evidentiary weight of WhatsApp chats, focusing on applicable regulations and judicial practices. Using case studies and juridical analysis, the study explores authentication and verification challenges for digital evidence—specifically WhatsApp conversations—in legal contexts. Results indicate that while Indonesia’s legal framework (including the ITE Law and PERMA No. 1 of 2024) recognizes electronic evidence, persistent issues include chat manipulation risks and non-standardized submission protocols. The paper emphasizes establishing technical standards for digital evidence and advocates for reinforced verification mechanisms. These findings carry significant implications for legal practitioners and policymakers, proposing regulatory and procedural enhancements to safeguard electronic evidence integrity within the judicial system.